Karakteristik Biopelet dari Tanaman Lamtoro (Leucanea leucocephala Lam) dan Gamal (Gliricidia sepium Jacq) pada Berbagai Variasi Komposisi dan Ukuran Partikel : Characteristics of Biopellet from Lamtoro (Leucanea leucocephala Lam) and Gamal (Gliricidia sepium Jacq) at Different Particle Size and Composition - Aprilia, Nurul; Yunianti, Andi Detti; S, Suhasman; Pari, Gustan (Forestry Faculty of Hasanuddin University, 2023)
Energy needs continue to increase, resulting in energy reserves decreasing yearly, especially those made from fossil fuels, which are non-renewable energy, so their availability is limited. Therefore, efforts are needed to find alternative energy sources that can be developed. An energy source that can be produced is biomass. Gamal (Leucanea leucocephala) and Lamtoro (Gliricidia sepium) plants are biomass often used as alternative raw materials for energy, namely biopellets, because they have high calorific value. This study aimed to determine the characteristics of biopellets from L. leucocephala and G. sepium with various compositions and particle sizes. The composition of the L. leucocephala and G. sepium raw materials is 1:1, 1:2, and 2:1 with a particle size that is passed 40 mesh retained 60 mesh, passed 60 mesh retained 80 mesh, and passed 80 mesh retained 100 mesh. Quality testing of biopellets based on SNI 8951:2020 includes density, moisture content, fly content, ash content, fixed carbon, and calorific value. The results showed that the biopellets were following SNI 8951:2020, namely the average value of density, moisture content, and ash content, for the parameters of the value of the flying substance content and fixed carbon were not in accordance. Statistics have shown that particle size significantly affects density, ash content, volatile matter, and fixed carbon. The composition affects the moisture content, fixed carbon, volatile matter content, and ash content. The best biopellets were produced in the treatment with 80 mesh particle size and 2:1 composition.